ELTV Channel 6 News (African Knowledges and the History Publication since the 1970s)
African cultural heritage; traditional lifestyles in modern Liberia; and medication, information-based, environmental, and economic interrelations and inequalities between Global North and South countries. Various contents relating to Germany.
Keywords: Politics; Local News; International News; Global North; Global South; Inequality